An Efficient Distributed Power Control with Linear Receivers for Asynchronous DS-CDMA Systems Subject to Propagation Delays - Luna-Rivera, J M; Campos-Delgado, D U (2010 IEEE 72nd Vehicular Technology Conference - Fall, 2010)
The vast literature on power control for CDMA systems ignored the fact that propagation delays occur inevitably during data communication between the base station and the mobile units or viceversa. If these delays are not considered into the power control design stage, the performance of the resulting feedback system can be severely deteriorated or even instability could be triggered in a practical scenario. In this paper, we extend the conventional power control framework to a more practical scenario that explicitly incorporate into the analysis: 1) the propagation delays while information is exchanged between the base station and the mobile terminals, 2) the asynchronous transmissions in the uplink channels, generally neglected in the literature for power control algorithms. This framework is then used to propose a distributed power control strategy enhanced with linear multiuser receivers. It is shown that through a proper selection of an error function, the nonlinear coupling among active users is transformed into individual linear loops. Simulation results show a remarkable performance improvement by using jointly power control and signal detection strategies. It is also shown that the proposed power control algorithm is particularly robust for keeping closed-loop stability despite transmission delays.